Complex Transformations to Solve Cosmological Constant Problem - Samy J. Litiloly (Industrial Engineering Study Program, Pattimura University, 2012)
In this paper, a new symmetry argument in a vacuum state with strictly vanishing vacuum energy has been studied. This argument exploits the well-known feature that deSitter and Anti-deSitter space are related by analytic continuation in complex analysis. When we drop boundary and hermiticity conditions on quantum fields, we get as many negative as positive energy states, which are related by transformations to complex space. In this case, we have explored indirectly a new perspective to solve cosmological constant problem.